2011
DOI: 10.1007/s00464-011-1940-6
|View full text |Cite
|
Sign up to set email alerts
|

Short esophagus: selection of patients for surgery and long-term results

Abstract: Short esophagus can be suspected during preoperative studies, and in this series, it was confirmed in 6.4% of the patients who had surgery. A Collis fundoplication procedure seems to be an adequate operation to control reflux symptoms and to avoid reherniation over the long-term follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This concept was based on reducing the undesirable postoperative side effects. Due to the severity of dysphagia and bloating, the Toupet fundoplication was routinely performed by some authors, regardless the esophageal manometry findings 1,28 . The effects of these treatments were reviewed in prospective studies which evaluated the results of a five-year surgical practice in 100 patients submitted to laparoscopic Toupet fundoplication regardless esophageal manometry findings 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept was based on reducing the undesirable postoperative side effects. Due to the severity of dysphagia and bloating, the Toupet fundoplication was routinely performed by some authors, regardless the esophageal manometry findings 1,28 . The effects of these treatments were reviewed in prospective studies which evaluated the results of a five-year surgical practice in 100 patients submitted to laparoscopic Toupet fundoplication regardless esophageal manometry findings 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the major causes of postoperative dysphagia, one study reported that the morphologic-anatomic causes of dysphagia might be attributed to the difficulties with hiatal closing in 90% of the cases and in only 10% to an inadequate fundoplication (too long or too tight), or the intrathoracic fundoplication migration was involved, possibly resulting in a partial or total disruption and obstruction 7 . The cases of recurrent or persistent dysphagia due to the so-called "slipped Nissen", induced by a partial or total disruption of the primary posterior hiatal repair were also reported 7,28 . In addition, postoperative dysphagia may largely be due to an excessively tight hiatal repair, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Within them are considered laparotomy and thoracotomy, and lately laparoscopic and thoracoscopic approach. These approaches are the subject of many studies that seek to determine whether there is an advantage over others in terms of providing an adequate length of intra-abdominal part of the esophagus with minimal post-operative complications (14,17). As an alternative method mentioned Collis gastroplasty which can be performed via laparotomy and by laparoscopy.…”
Section: Procedures Approachesmentioning
confidence: 99%
“…This method has been criticized because of the presence of parietal cells that secrete gastric acid in neoesophagus and because of reduced motility that allows direct contact between the acidic contents and mucosa of the esophagus (1,11,19). Despite this gastroplasty and fundoplication can be effective in controlling symptoms of the reflux (10,17). Traditionally, in patients with suspected syndrome of short esophagus is conducted transthoracic fundoplication because this approach provides ideal conditions for the mobilization of the esophagus and allows Collis gastroplasty when it is needed.…”
Section: Procedures Approachesmentioning
confidence: 99%
“…Horvath and his coworkers divided the short esophagus into three categories: 1) a true, nonreducible short esophagus; 2) a true, but reducible short esophagus; 3) an apparent short esophagus (4). Early reports in the literature show the different frequency in patients with esophageal disease, from 0% (by Hill and his coworkers) to 60% (by Pearson and his coworkers) (the data collected for the time period 1980-1991) (2,3,5,6). Most data are based on the methods of precise gastroesophageal junction determination as well as the subjective gradation tension needed for the reposition of the suitable esophagus segment placed under the diaphragm.…”
Section: Introductionmentioning
confidence: 99%